2024 CGIAR Climate Impact Platform Communications Plan - Edward-Uwadiale, Regina; Mukherji, Aditi (CGIAR System Organization, 2024)
The primary objective of the Climate Impact Platform's communications is to position CGIAR as a foremost authority in climate change adaptation and mitigation within agricultural and food systems. Our aim is to seamlessly integrate CGIAR's cutting-edge research into national, regional, and global initiatives focused on reducing emissions, strengthening adaptive capabilities, and fostering equitable transitions within agrifood systems.